Differences in the Content Knowledge of Those Taught to Teach and Those Taught to Play - DERVENT, FATİH (HUMAN KINETICS PUBL INC, 2018)
Purpose: Little is known about how teachers acquire specialized content knowledge (SCK). We examine the hypothesis that SCK is not acquired from K-12 physical education and from extracurricular activities characterized by playing; instead, SCK must be explicitly taught to teachers. Method: Students were enrolled in either basic physical activity instruction classes (n = 119), where the focus of instruction was on learning to play (common content knowledge), or physical education teacher education movement classes (n = 72), where the focus of instruction was on learning to teach (SCK). Content maps were used to assess the SCK of the study participants prior to and after receiving instruction in badminton, tennis, basketball, and volleyball. Results: Non-parametric statistics showed significant differences in pretest scores. However, these differences were determined to be not meaningful. Pre-post gains were significant for both groups but, meaningfully different only for the teaching group. Discussion: Findings demonstrate that (a) SCK is not acquired in any depth from engagement in K-12 physical education and extracurricular experiences, and (b) can be explicitly taught to teachers.
Keywords: content knowledge; pedagogical content knowledge; specialized content knowledge; teacher education; PEDAGOGICAL CONTENT KNOWLEDGE; PHYSICAL-EDUCATION; CONCEPTIONS